The Effectiveness of Vitamin E Soft Capsules as an Antioxidant - Putri, Syakirah Yasmin; Isadiartuti, Dewi; Isnaeni, Isnaeni; Aulya Farah Fahreza; Alvina Violita Mulyanto Putri; Zulfa Diana; Nafa Nazilatul Fatihah; I Gede Rekyadji Arimbawa; Alya Fakhirah; Talitha Nabilla Wijayanata; Muhammad Pramudya Pangestu; Azzalia Firdanthi; Oudrey Addriana; Umi Aida Rohma (Berkala Ilmiah Kimia Farmasi, 2024)
Antioxidants inhibited the oxidation of other molecules and played an important role in maintaining a healthy body. Antioxidants were found in fruits, vegetables, all parts of plants, and were present in the body as enzymes or products of metabolism. Vitamin E referred to a large number of natural or synthetic compounds, with alpha-tocopherol being the most active and widely distributed form in nature. Alpha-tocopherol was the most active antioxidant form of vitamin E and served as the primary lipophilic antioxidant in plasma, membranes, and tissues. The most important function of vitamin E was its antioxidant capability, counteracting free radical attacks that could damage cells and cause various degenerative diseases. Additionally, antioxidants helped reduce the effects of photoaging on the skin, potentiated anti-aging and anti-inflammatory activity, increased the rate of wound healing, and helped maintain healthy eyes and the immune system. One form of vitamin E dosage form was a soft capsule, which had several advantages, including the ease of filling the Active Pharmaceutical Ingredient (API) in liquid form, higher production capacity, and formulation uniformity compared to gelatin tablets or hard capsules. Soft capsule preparations also had rapid API release, which could result in achieving therapeutic blood levels more quickly and achieving greater bioavailability. This study aimed to evaluate soft capsule dosage forms in enhancing the effectiveness of vitamin E as an antioxidant. The research utilized review articles sourced from national and international journals, as well as scientific journals. The results showed that vitamin E supplementation in soft capsules could increase its effectiveness as an antioxidant.Keywords:  Soft Capsule, Increase Effectiveness, α-tocopherol, Vitamin E, Antioxidant